(untitled) (Academia Science Repository, 2023)
This article provides information on the evolution, development and stages of development of spiritual and educational broadcasts on national radio. Issues such as coordinating the activities of state bodies, non-governmental organizations and working (expert) groups in the main areas of spiritual and educational work in our country were considered.